Analisis Tren Pergerakan Harga Saham pada Indeks LQ45 di Bursa Efek Indonesia - Dionisius Dwiki Dharmawan; Mutiara Maimuna (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study aims to analyze stock price trends in companies included in the LQ45 index on the Indonesia Stock Exchange during the 2020–2024 period. The LQ45 index is a collection of stocks of companies with high liquidity and large market capitalization, often used as a benchmark for assessing stock market conditions in Indonesia. Fluctuating stock prices necessitate trend analysis to determine the direction of stock movements. This study uses a quantitative method with a descriptive approach. The data used are secondary data in the form of monthly closing prices obtained from official sources such as the Indonesia Stock Exchange and online financial platforms. The research sample was determined using a purposive sampling technique, namely companies consistently included in the LQ45 index and with complete data, such as PT Bank Central Asia Tbk (BBCA), PT Bank Rakyat Indonesia Tbk (BBRI), PT Bank Mandiri Tbk (BMRI), and PT Telkom Indonesia Tbk (TLKM). The data analysis techniques used are descriptive analysis and trend analysis to identify the direction of stock price movements, whether they are showing an uptrend, a downtrend, or a stable movement. The research results are expected to provide an overview of the stock price movement patterns of companies included in the LQ45 index and provide useful information for investors and researchers in understanding stock market conditions in Indonesia